Classification of Soil Distribution on the Island of Saparua Based on the Soil Classification System National and the Equivalent to Soil Taxonomy - Risamasu, Robby. G. (Future Science / FSH-PH Publications, 2023)
This research aims to classify the distribution of soils on Saparua Island, Central Maluku Regency, based on the Subardja, D, et al, (2016) and soil taxonomy (SSS, 2022). The benefit of this research is to find out the distribution of soils on Saparua Island to support the regional development plan. The method used is the survey method, with a semi-detailed survey level of a 1:50,000 scale. The pattern of the approach used is a physiographic analysis approach to landscapes, in which the research area is divided into terrestrial units based on the similarity of the properties of the variables that influence soil formation. The base map used in this study is a land unit map with a scale of 1:50,000. The results showed that the factors and processes involved in soil formation in the study area were parent material and topography, leaching, and eluviation processes. The soils found consisted of seven types of soil with 11 subgroups, namely: Regosol Eutric (Typic Udipsamments and Lithic Udipsamments), Litosol (Lithic Udorthents), Kambisol Distrik (Typic Dystrudepts), Kambisol Litik (Lithic Eutrudepts), Gleisol Eutrik (Typic Endoaquents and Aquic Eutrudepts), Gleisol Distrik (Typic Haplaquepts), Podsolik Kandik (Typic Hapludults and Typic Kandik), and Organosol Hemik (Hydric Tropohemists) were also found.